PENGARUH PEMBELAJARAN DALAM DARINGAN (DARING) TERHADAP MINAT BELAJAR MAHASISWA FAKULTAS EKONOMI PRODI MANAJEMEN UNIVERSITAS SISINGAMANGARAJA XII TAPANULI TAHUN AJARAN 2020/2021 - Santiria Eska Lestari Manik; Herta Manurung; Hotlin Siregar; Leonard R Sinaga (JURNAL GLOBAL MANAJEMEN, 2021)
This study aims to determine the effect of online learning on students' interest in learning from the economics faculty of the management study program at Sisingamangaraja XII Tapanuli University in the 2020/2021 academic year.The population in this study were all students of the Economics Faculty of Stambuk 2016-2020, and the sample was 79 respondents, using the "Proportionate Stratified Random Sampling" sampling technique. The research design used is quantitative research, and data collection is in the form of observations and questionnaires. Meanwhile, for data processing, it was analyzed to test the validity and reliability using computer assistance with SPSS 21.0 for windows program.The results obtained from the correlation coefficient test with a positive and significant relationship between the variables of Online Learning (X) and Learning Interest (Y) Students of the Faculty of Economics Management Study Program Sisingamangaraja XII Tapanuli University Academic Year 2020/2021. This is evidenced by the correlation coefficient of 0.613 with a strong relationship level category. The results of the R Square Determination Test are 0.375 or 37.50%. This shows that the effect of Online Learning (X) on Learning Interest (Y) of Students of the Faculty of Economics Management Study Program, Sisingamangaraja University XII Tapanuli for the 2020/2021 Academic Year is 37.50% and the remaining 62.50% is influenced by other factors.The results of simple linear regression calculations Y = 6.822 + 0.811 in the sense that if the value of learning dares to increase by 1, the interest in learning increases by 0.811.The test results are known through tcount (6,803) > ttable (1,664), it can be said that it has been accepted that Dare Learning has a positive and significant influence on student interest in learning at the Faculty of Economics Management Study Program, Sisingamangaraja XII Tapanuli University, Academic Year 2020/2021.